2018
DOI: 10.1039/c7cc08927a
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) on homogeneous photocatalytic reduction of CO2

Abstract: A significant decrease in the amount of the sacrificial electron donor triethanolamine (TEOA) required for the homogeneous photocatalytic reduction of CO2 using rhenium-based catalytic systems can be achieved by adding small quantities of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) to the reaction mixture. The turnover numbers (TONs) and frequencies (TOFs) measured for the reactions described herein are even higher than those observed in reaction mixtures containing high concentrations of TEOA. Furthermore, repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous works ascribed limited photostability of fac- ReX­(CO) 3 (bpy)-type CRCs to three deactivation pathways of the one-electron reduced species (OERS) (Figure a): , OERS reaction with a radical species (TEOA ox ) from TEOA oxidation, , OERS moiety dimerization forming an unreactive species, and OERS photoexcitation leading to decomposition …”
Section: Resultsmentioning
confidence: 99%
“…Previous works ascribed limited photostability of fac- ReX­(CO) 3 (bpy)-type CRCs to three deactivation pathways of the one-electron reduced species (OERS) (Figure a): , OERS reaction with a radical species (TEOA ox ) from TEOA oxidation, , OERS moiety dimerization forming an unreactive species, and OERS photoexcitation leading to decomposition …”
Section: Resultsmentioning
confidence: 99%
“…About 1 M TEA was sufficient to induce ∼90% irreversibility in the photoreduction of the Ru­(CO)­(H) + complex, while the stronger bases, HCOO – and DBU, only required a few tens of millimolar concentration. Indeed, a recent study has shown that substitution of molar concentrations of TEOA with millimolar levels of DBU more than doubled the overall photocatalytic performance for the reduction of CO 2 to CO with rhenium-tricarbonyl-type catalysts …”
Section: Resultsmentioning
confidence: 99%
“…We thus need an electron donor which does not absorb in the visible range and does not easily coordinate to Re. The sacrificial electron donor molecule 1,3-dimethyl-2-phenylbenzimidazoline (BIH) was prepared following a published procedure and used in combination with DBU (1,8-diazabicyclo[5.4.0]­undec-7-en) as a non-nucleophilic base . DBU can deprotonate the BIH •+ radical cation more efficiently (at much lower concentration) than commonly used TEOA (triethanolamine) and increase the yield of reduced ReP ∩ N •– by a second electron transfer to ground state ReP ∩ N , while also limiting electron back transfer to BIH •+ from ReP ∩ N •– . , To initiate the photoreaction, we excited the charge transfer bands of ReP ∩ N and ReAs ∩ N and recorded transient infrared spectra in the carbonyl stretch region over 10 orders of magnitude in time.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure c,d, one can see that upon further addition of DBU as a base, both ground state bleach of ReP ∩ N as well as the positive band of ReP ∩ N •– are increasing again on a 1–10 μs time scale. This is the result of direct electron transfer to ground state ReP ∩ N from BI • , which was formed via deprotonation of BIH •+ , , thus significantly increasing the yield of ReP ∩ N •– for the investigation of its reactivity. However, in the time window covered by the trIR measurement shown in Figure (up to 40 μs), the addition of CO 2 did not result in significant changes of the signal.…”
Section: Resultsmentioning
confidence: 99%